Validation and Investigation of Sentence Parsing Strategies: a Study of EFL Learners Psych and Language Processing (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Having a proper insight into understanding the human cognition in sentence processing strategies, this study explored the nature of Minimal Attachment and Late Closure strategies in relation to language proficiency levels. Facing the problem that why some EFL learners tend to parse differently (i.e., use Minimal Attachment and Late Closure Strategies), on one hand and the need to develop a reliable and valid instrument to do the respective investigation on the other hand, was the motive behind this study. By administering a Preliminary English Test (PET), three groups of Iranian adult EFL learners, both male and female were conventionally classified into three levels of proficiency. Three separate researcher-made sentence comprehension tests (each for one proficiency level) were then adopted as the main data collecting instruments through applying Think- Aloud Protocol in which all steps of instrument validation were taken. Findings revealed the use or better to say construct validity of various strategies. Meanwhile, the analyses revealed that the parsing strategies are, to some extent if not that much, associated with language proficiency levels, indicating that language proficiency level has some degree of effect on the participants use of parsing strategies as a whole, although findings on Minimal Attachment and Late Closure strategy use as two separate ones differed. While, there was not much effect of language proficiency level on Minimal Attachment strategy, the findings indicated a moderately large effect size on Late Closure strategy use and the three groups showed almost higher means on Late Closure strategy rather than the other one. Therefore, certain parsing strategies are associated with language proficiency level proving the fact that language proficiency level is an effective parameter as far as human cognition in language processing in general and sentence processing in particular are concerned. Moreover, not only is there relationship among language proficiency levels and the strategy use but the nature of relationship varies depending on language proficiency level and strategy type.